Development of Genially Interactive Multimedia on Materials for the National Movement Organization for Middle School Students - Kristoforus Bagas Romualdi; Ajat Sudrajat; Aman Aman (STAI Hubbulwathan Duri, 2023)
This study aims to produce interactive multimedia learning using the Genially application on the subject matter of national movement organizations for grade VIII junior high school students. The stages in this research and development adopt the ADDIE method: analysis, design, development, implementation, and evaluation. The results showed that based on the validation findings of material experts, who gave an average score of 4.7, media experts gave an average score of 4.1, and the validation of the two teachers revealed an average score of 4.3. The media developed by researchers in small-scale trials obtained an average score of 4.25 or very feasible criteria during the implementation phase. At the implementation stage, researchers conducted a limited trial involving 15 class VIII students of SMP Negeri 4 Sijuk. In the results of this implementation phase, students give an assessment with the